Pendampingan Pengolahan Limbah Kulit Pisang Menjadi Sabun Cuci Piring Bagi Kelompok Usaha Waroh Maju Bersama Di Desa Sesaot Lombok - Hasbi, Nurmi; Eskarani Tri Pratiwi; Nisa Isnaeni Hanifah; Rosyunita; Ni Wayan Puspa Wijaya Suryantarini; Syahrani Febriyanti; Muthiah Ramadhani (Universitas Mataram, 2025)
Community service activities were carried out in Sesaot Village, Narmada District, West Lombok Regency, which is known as a banana production center with a fairly large production volume on Lombok Island. One of the processing groups is Usaha Waroh Maju Bersama, which is engaged in the production of banana-based souvenirs, such as banana chips, banana sale, and various other processed products. However, this processing activity produces banana peel waste that has so far been thrown away. In fact, banana peels contain phytochemical compounds such as saponins and flavonoids that have the potential to be used as antibacterial agents. This community service aims to provide assistance to Usaha Waroh Maju Bersama to process banana peel and lime waste into antibacterial dishwashing soap. This activity was carried out on Friday, August 8, 2025. The service method used was mentoring through demonstrations. This activity was attended by 11 participants, all of whom were women, the majority aged 26-50 years. The educational background of the participants varied, dominated by junior high and high school graduates. The evaluation results showed a positive response: 81.8% of participants strongly agreed that the material was easy to understand, 90.9% considered the resource person to have delivered the material clearly, and 72.7% felt the practice was easy to follow. No participants disagreed, so it can be concluded that the activity was effective. Participants said that the steps for making soap were quite simple, practical, and easy to apply at home. Most participants expressed a desire to participate in follow-up activities with different topics such as making skin care products from natural ingredients or utilizing other fruit waste. This community service activity succeeded in increasing community skills and awareness in processing banana peel waste into healthy, environmentally friendly, and economically valuable household products.